Numerical and analytical investigation of tensile behavior of non-laminated and laminated CFRP straps. (15th September 2018) - Fan, Haifeng; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract: The tensile behavior of non-laminated and laminated CFRP straps composed of up to 100 layers was numerically and analytically investigated. The failure mode in non-laminated straps changed at 20–30 layers from brittle and sudden rupture of the outermost layer to progressive rupture starting from the innermost layer, due to the different non-uniform strain distributions across the layers. Non-laminated straps showed a significantly higher load-bearing efficiency for layer numbers higher than 20 and exhibited lower sensitivity to tape anisotropy and friction at the strap/pin interface than laminated straps. An empirical model was established to estimate the ultimate load of non-laminated straps with up to 100 layers and an analytical model was derived to predict the load-bearing efficiency of laminated straps, taking into account the strap anisotropy and friction at the strap/pin interfaces.